The Effects of Governance Dynamics on the Performance of Primary Education in Mukono District - Laetisha Seth Asio (Uganda Christian University, 2024)
The study was focused on the effects of governance dynamics on the performance of primary education in mukono district examined how governance practices influenced primary education outcomes in Mukono District. The study aimed to evaluate transparency in decision-making, community involvement, and accountability mechanisms, and their impact on key performance indicators such as enrollment rates, academic achievement, and infrastructure quality. By surveying respondents from diverse educational roles, the research revealed significant challenges, including inadequate transparency, mixed effectiveness of accountability mechanisms, and limited community engagement. The findings emphasized the need for improved governance practices to enhance educational outcomes. Recommendations included increasing transparency, strengthening accountability, boosting community participation, and better resource allocation to address governance gaps and improve primary education performance in Mukono District.
Undergraduate research